Cryogenic performances of a heat exchanger prototype suitable for the superconducting HL-LHC recombination dipole D2. Issue 1 (1st May 2022) - Rousset, B; Bancel, F; Besson, N; Bon-Mardion, M; Claudet, S; Goy, T; Millet, F; Nivelon, P; Perin, A
Abstract: In the framework of the future High Luminosity upgrade of the Large Hadron Collider (HL-LHC) at CERN, most superconducting magnets in the Long Straight Sections will be replaced. Among them, the new D2 recombination dipole will be a He II conduction-cooled magnet with a larger aperture than the LHC dipoles. To provide the required cooling (up to 70 W) to the D2 and to comply with its cryostat integration constraints, a compact heat exchanger was designed by the CEA Département des Systèmes Basses Températures (DSBT) based on a CERN preliminary analysis and a CEA review of the possible cooling schemes. This heat exchanger provides the required heat transfer between the He II pressurized bath and the He II saturated bath to cool the D2 magnet in different operating conditions at 1.8 K and 2 K. The detailed design of the heat exchanger was defined and one prototype was manufactured by industry under the CEA supervision. The heat exchanger prototype is composed of roughly one hundred oxygen-free high purity copper tubes, electron beam welded to the stainless steel He II bath enclosure. The present paper describes the successful cryogenic performance tests of the prototype of the D2 heat exchanger measured in the CEA 400W@1.8K test facility in Grenoble.